2018
DOI: 10.1038/s41433-018-0226-9
|View full text |Cite
|
Sign up to set email alerts
|

Enucleation in Asian Indian patients: a histopathological review of 2009 cases

Abstract: Objective To review the indications of enucleation in Asian Indian patients and study the trend over the 22-year period. Methods Retrospective study of 2009 patients who underwent enucleation. Results The mean age at presentation of patients who underwent enucleation was 155 months The histopathology diagnosis included a benign tumor (n = 22, 1%), malignant tumor (n = 1472, 73%), acute trauma (n = 93, 5%), retinal vascular disease (n = 50, 3%), inflammatory/infective pathology (n = 33, 2%), or other miscellane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
3
5
1
Order By: Relevance
“…In contrast to previous studies [6,7,9], our data showed a slight predominance of females undergoing enucleation, compared to males (51.4% vs. 48.6%). Trauma as a primary enucleation indication was more common among male than female patients (67.4% vs. 32.6%), similar to the findings of de Gottrau et al (79% vs. 21%) [3], Freitag (75% vs. 25%) [10], and Cheng (81.3% vs. 18.7%) [4].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to previous studies [6,7,9], our data showed a slight predominance of females undergoing enucleation, compared to males (51.4% vs. 48.6%). Trauma as a primary enucleation indication was more common among male than female patients (67.4% vs. 32.6%), similar to the findings of de Gottrau et al (79% vs. 21%) [3], Freitag (75% vs. 25%) [10], and Cheng (81.3% vs. 18.7%) [4].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the number of enucleations with tumours did not decrease over time in the literature [9, 12]; a similar result was observed in our series (Figure 4) [15,16]. Similar to the findings of our study, tumours were also reported as the leading causes of enucleation in France [17], Turkey [8], and India [7] in 1996, 1997, and 2018, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations